Allelic Imbalance in TOR1A mRNA Expression in Manifesting and Non-Manifesting Carriers of the GAG-Deletion - Armata, Ioanna A.; Diplas, Andreas I.; Ozelius, Laurie J.; Shashidharan, Pullanipally (Journal of Nucleic Acids, 2012)
Early onset dystonia (EOD) is associated with a 3bp-(ΔGAG) in-frame deletion in the TOR1A gene, which encodes for torsinA. Carriers of the mutant (ΔGAG) allele can either develop or escape a dystonic phenotype (~30% penetrance). The expression ratio of the two alleles could be important for the manifestation or prevention of the disease since wild-type (WT) torsinA is thought to have protective function. Absence of an antibody discriminating WT from ΔE torsinA has precluded the determination ΔE and WT torsinA levels in manifesting and nonmanifesting carriers. We performed quantitative analysis of TOR1A allele expression in manifesting (MC) and nonmanifesting (NMC) carriers using quantitative allele-specific PCR (qASPCR) to determine the levels of mutant versus WT torsinA mRNA. The technique described showed high degree of specificity in detecting the two alleles. The present study represents the first comprehensive analysis of biallelic expression of the TOR1A gene in lymphoblast and brain samples from patients and NMC relatives. We demonstrate that mRNA is transcribed from both the WT and ΔGAG allele in peripheral and neural tissues with a trend for increased expression of the ΔGAG allele compared to the WT in carriers regardless of their phenotype and thus cannot account for the reduced penetrance.